PENINGKATAN KUALITAS PEMBELAJARAN PKn MELALUI MODEL KOOPERATIF TIPE TGT MENGGUNAKAN MEDIA AUDIOVISUAL - Lase, Asmawati (JURNAL PENA EDUKASI, 2018)
Abstract: This type of research is Classroom Action Research (CAR). The subjects in this study were teachers and students of Class III / a SD Negeri 070977 Gunungsitoli, as many as 41 students consisting of 28 male students and 13 female students. The application of the TGT cooperative model using audiovisual media is able to improve the quality of learning in Civic Class III / a Gunungsitoli 070977 Public Elementary School. Quality improvement is indicated by increasing teacher skills, student activities, and student learning outcomes. This research was conducted in three cycles with each cycle consisting of one meeting. Learning outcomes data in the first cycle reached classical completeness of 68.29% and experienced an increase of 29.37% from the initial condition. In the implementation of the second cycle of action obtained classical completeness of 78.05%. Furthermore, in the implementation of the action of the third cycle obtained the completeness of learning outcomes in a classical manner amounting to 85.37% and has achieved a predetermined success indicator, namely, 80% with KKM in Civics subjects amounting to 62. Keywords: Quality of Learning, TGT Abstrak: Jenis Penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subyek dalam penelitian ini adalah guru beserta siswa Kelas III/a SD Negeri 070977 Gunungsitoli, sebanyak 41 siswa yang terdiri atas 28 siswa laki-laki dan 13 siswa perempuan. Penerapan model kooperatif tipe TGT dengan menggunakan media audiovisual mampu meningkatkan kualitas pembelajaran PKn Kelas III/a SD Negeri 070977 Gunungsitoli. Peningkatan kualitas tersebut ditunjukkan dengan meningkatnya keterampilan guru, aktivitas siswa, serta hasil belajar siswa. Penelitian ini dilaksanakan dalam tiga siklus dengan masing-masing siklus terdiri atas satu pertemuan. Data hasil belajar pada siklus I mencapai ketuntasan klasikal sebesar 68,29% dan mengalami peningkatan 29,37% dari kondisi awal. Pada pelaksanaan tindakan siklus II diperoleh ketuntasan klasikal sebesar 78,05%. Selanjutnya, pada pelaksanaan tindakan siklus III memperoleh ketuntasan hasil belajar secara klasikal sebesar 85,37% dan telah mencapai indikator kaberhasilan yang telah ditetapkan yaitu, 80% dengan KKM pada mata pelajaran PKn sebesar 62. Kata kunci: Kualitas Pembelajaran, TGT